Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Pregnancy. A Non-systematic Review of Clinical Presentation, Potential Effects of Physiological Adaptations in Pregnancy, and Placental Vascular Alterations - Ayala-Ramírez, Paola; González, Marcelo; Escudero, Carlos; Quintero-Arciniegas, Laura; Giachini, Fernanda R.; Alves de Freitas, Raiany; Damiano, Alicia E.; García-Robles, Reggie (Frontiers in Physiology, 2022)
In December 2019, the novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) rapidly spread to become a pandemic. To date, increasing evidence has described the potential negative impact of SARS-CoV-2 infection on pregnant women. Although the pathophysiology of coronavirus disease 2019 (COVID-19) is not entirely understood, there is emerging evidence that it causes a severe systemic inflammatory response associated with vascular alterations that could be of special interest considering some physiological changes in pregnancy. Additionally, these alterations may affect the physiology of the placenta and are associated with pregnancy complications and abnormal histologic findings. On the other hand, data about the vaccine against SARS-CoV-2 are limited, but the risks of administering COVID-19 vaccines during pregnancy appear to be minimal. This review summarizes the current literature on SARSCoV2 virus infection, the development of COVID19 and its relationship to physiological changes, and angiotensin-converting enzyme 2 (ACE2) function during pregnancy. We have particularly emphasized evidence coming from Latin American countries.